Anatomia, histoqu?mica e arquitetura foliar de Chrysophyllum rufum Mart. (sapotaceae) ocorrente no semi?rido baiano - Santos, R?sia Cean Silva de Lima (2019)
Sapotaceae is a family of pantropical trees and shrubs, with great diversity in South America, being economically prominent in food, folk medicine and the timber industry. According to the most recent classification, the family is subdivided into three subfamilies, Sarcospermatoideae, Sapotoideae and Chrysophylloideae, the latter being composed of 25 genera. Chrysophyllum L. is the second largest genus of Chrysophylloideae, with 81 neotropical species. In Brazil it is represented by 31 species occurring in the various plant formations, of which 14 species are endemic. Among the endemic species, Chrysophyllum rufum Mart. occurs in forest formations of the Bahian semi - arid, being represented by individuals that can reach up to 20m in height, characterized by the rusty dress on the abaxial face of the leaves and sepals, and small greenish flowers. Due to the lack of morpho-anatomical studies for the family, the objective was to characterize the leaves of Chrysophyllum rufum through anatomical, histochemical and foliar architecture studies, in order to contribute to the correct identification of the species and the obtaining of subsidies for more specific studies. The study was carried out with adult leaves collected in municipalities inserted in the Bahian semi - arid region. Cross sections of the petiole and leaf blade were obtained through free hand cuts and treated according to the specific bibliography. Histochemical tests detected starch, lignin, phenolic compounds, reducing sugars, calcium oxalate crystals, mucopolysaccharides, pectins and mucilages. In the anatomical analyzes, it was possible to verify the shape of the petiole, presence of malpiguiaceous trichomes, types of stomata, dorsiventral mesophyll, calcium oxalate crystals and laticifers. The venation pattern was evaluated after diaphanization, being constant in all samples and compatible with that described for the family. The studies carried out aim to provide sufficient elements to support other research.